Using Statistical Quality Control Charts for Measuring Educational Service Quality at Sebha University from the Viewpoint of Students - علي خير صابر و حافظ ابوبكر امحمد و نوارة محمد الفيتوري (Journal of Pure & Applied Sciences, 2019)
The aim of this study is to identify the quality of the educational services provided by the Faculty of Science, University of Sebha, Libya to its students. For evaluating these services the statistical control charts of the variables, which include the Mean chart, the standard deviation chart as well as the double charts (mean and standard deviation) have been used. A simple random sample of 200 students from the Faculty of science Sebha was used for collecting the study data. The collection tool was the actual service performance (ServPerf) measuring questionnaire that is an appropriate to measure the quality of the educational service that comprises of six dimensions. Data analysis and statistical control charts were carried out using Minitab (ver. 18). The results showed that the quality of the educational service below the expected level and that there are weakness and variability in the levels of services quality that are provided to students according to the considered dimensions. As well as it was possible to identify the factors are contributing to the low level of quality of educational services for each dimension from the viewpoint of students. The current study implies some recommendations including: to take into account the negative aspects of services to enhance the quality of university services in all its forms and to pay attention to the positive aspects of the educational services provided by the faculty and work toward strengthen them.